PENINGKATAN NILAI TAMBAH WISATA PANTAI MELALUI TRANSPLANTASI KARANG DI PANTAI TAMAN KOTA KELURAHAN BALELA - Brigita Elisabet KR. Uran; Mudmainna Mudmainna; Reinaldis Masi (LPPM Institut Pendidikan Nusantara Global, 2025)
The degradation of coral reef ecosystems in Indonesia’s coastal areas, including Balela Village, Larantuka District, East Flores Regency, has become a serious problem affecting the ecological, social, and economic aspects of coastal communities. The lack of community awareness regarding the importance of coral reef conservation and the limited utilization of marine tourism potential further worsen this condition. This Community Service Program (PkM) aims to enhance community awareness, knowledge, and skills in environmental conservation while optimizing the added value of coastal tourism through coral transplantation. The implementation method was designed in three stages: planning, implementation, and evaluation, involving lecturers and students of the Larantuka Institute of Teacher Training and Technology together with the Balela community. The activities included educational sessions, interactive discussions, hands-on coral transplantation using hexagonal dome-shaped iron frames, as well as observation and interviews for evaluation. The results showed significant improvements in participants’ knowledge, attitudes, and skills related to marine conservation; the growth of collective awareness to maintain beach cleanliness; and the emergence of marine tourism-based business opportunities with the potential to increase household income. Despite challenges such as limited facilities and unfavorable weather conditions, active community participation and support from local government were key factors in the program’s success. In conclusion, coral transplantation combined with an educational-participatory approach has proven effective not only in restoring marine ecosystems but also in promoting coastal community empowerment towards sustainable economic development.